2018
DOI: 10.24908/pceea.v0i0.13054
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Escape Room Popularity to Provide First-Year Students with an Introduction to Engineering Information

Abstract: Incoming first-year engineering students at the University of Toronto often have difficulty navigating the library and its resources. Orientation activities at the Engineering & Computer Science Library are designed to introduce students to the library in an informal and entertaining way. In 2017, as a result of dropping interest in previous years' orientation activities, librarians at the Engineering & Computer Science Library collaborated with instructors and staff in the Faculty of Applied Science a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…However, to the knowledge of the authors, no works have been reported in the computer programming field. In addition to the previous ones, there have been other initiatives targeted to college students that foster informal learning such as earthquake-preparedness [22], or as a welcome activity for students to get to know institutional services [23], [24]. Some instructors have also conducted purely leisure escape rooms (whose puzzles do not integrate any educational content) with the sole aim of practising soft skills such as teamwork, leadership and communication [6], [7].…”
Section: Related Workmentioning
confidence: 99%
“…However, to the knowledge of the authors, no works have been reported in the computer programming field. In addition to the previous ones, there have been other initiatives targeted to college students that foster informal learning such as earthquake-preparedness [22], or as a welcome activity for students to get to know institutional services [23], [24]. Some instructors have also conducted purely leisure escape rooms (whose puzzles do not integrate any educational content) with the sole aim of practising soft skills such as teamwork, leadership and communication [6], [7].…”
Section: Related Workmentioning
confidence: 99%
“…In recent years, escape rooms have drawn the attention of educators and organizations in the cultural sector, which has led to these activities being used for educational purposes, not only in museums [4]- [7] and libraries [8], [9], but also in formal learning scenarios as part of the curriculum. In addition to using ludic escape rooms in educational settings, teachers have started to create actual educational escape rooms: escape rooms that require students to master field-specific knowledge and skills in order to solve the puzzles and succeed in the activity.…”
Section: Introductionmentioning
confidence: 99%
“…Case Studies, Real-World Labs, Service Learning [26], [32], [15], [17], [28], [34], [31], [35] Course Delivery [26], [27], [29], [36], [37], [30], [33], [38], [39] Assessment [13], [16], [40], [41], [22], [42], [23], [43], [44] Theory Based or Survey Results [11], [45], [46], [47], [10], [19], [48], [1], [39], [49], [24], [25], [50], [51], [52] Out-of-class activities [53], [54], [55], [56], [57], [58] While there have been many successful interventions that improved student motivation discussed in the CEEA 2010-2018 proceedings, the relevant motivation theory behind each intervention is often missing. Understanding motivation theory may not be necessary ...…”
Section: Type Of Interventionmentioning
confidence: 99%